(untitled) (Iter, 2022)
In contemporary theoretical reflection, reference to ethics and care of the self from a Hellenic background or inheritance is frequent as a way of expressing statements related to the relationship between ethics and politics. Although this topic has been approached by a large number of authors, it is uncommon to systematize and compare it with respect to the way each author refers to this problem. Responding to this need, the present article proposes a review of the arguments offered by three contemporary authors (Arendt, Foucault and Nussbaum) and a brief comparison on the ways in which the Hellenic heritage is reinterpreted.